PENGARUH PEMASARAN LANGSUNG TERHADAP PERILAKU KONSUMEN BISNIS MENGGUNAKAN MEETING PACKAGE DI GRAND TJOKRO HOTEL BANDUNG - Candra Fatihah, Dian; Rani Desmawati, Dewi (Politeknik Dharma Patria Kebumen, 2019)
This research is aimed to determine The Influence of Direct Marketing to Business Consumer Behavior Using Meeting Package at Grand Tjokro Hotel Bandung. Respondents from this research are 44 consumers selected by simple random sampling. This research used quantitative methods with approach descriptive analysis. Data was collected through survey, questionnaires and interviews. The test results validity and reliability variables X and Y are valid and reliable. The data analysis used statistical test of correlation pearson product moment and the coefficient of determination. Calculated used SPSS version 21. The data of this research is obtained from consumer data Grand Tjokro Hotel Bandung. From the result obtained correlation coefficient of 0,633. This tells that there is strong relation between Direct Marketing of Business Consumer Behavior. The influence of Direct Marketing to Business Consumer Behavior to 40,0% and remaining 60,0% is influenced by other factors not examined. The problems are competition between hotels is very tight, lack of coordination between sales. The suggestions given to fix the problem are 1) Do a better promotion to attract the attention of consumers; 2) Evaluation between Manager and Sales especially in Sales and Marketing Division.